Defining the Inflammatory Microenvironment in the Human Cochlea by Perilymph Analysis: Toward Liquid Biopsy of the Cochlea - Warnecke, Athanasia; Prenzler, Nils K.; Schmitt, Heike; Daemen, Kerstin; Keil, Jana; Dursin, Martin; Lenarz, Thomas; Falk, Christine S. (Frontiers in Neurology, 2019)
The molecular pathomechanisms in the majority of patients suffering from acute or progressive sensorineural hearing loss cannot be determined yet. The size and the complex architecture of the cochlea make biopsy and in-depth histological analyses impossible without severe damage of the organ. Thus, histopathology correlated to inner disease is only possible after death. The establishment of a technique for perilymph sampling during cochlear implantation may enable a liquid biopsy and characterization of the cochlear microenvironment. Inflammatory processes may not only participate in disease onset and progression in the inner ear, but may also control performance of the implant. However, little is known about cytokines and chemokines in the human inner ear as predictive markers for cochlear implant performance. First attempts to use multiplex protein arrays for inflammatory markers were successful for the identification of cytokines, chemokines and endothelial markers present in the human perilymph. Moreover, unsupervised cluster and principal component analyses were used to group patients by lead cytokines and to correlate certain proteins to clinical data. Endothelial and epithelial factors were detected at higher concentrations than typical pro-inflammatory cytokines such as TNF-a or IL-6. Significant differences in VEGF family members have been observed comparing patients with deafness to patients with residual hearing with significantly reduced VEGF-D levels in patients with deafness. In addition, there is a trend towards higher IGFBP-1 levels in these patients. Hence, endothelial and epithelial factors in combination with cytokines may present robust biomarker candidates and will be investigated in future studies in more detail. Thus, multiplex protein arrays are feasible in very small perilymph samples allowing a qualitative and quantitative analysis of inflammatory markers. More results are required to advance this method for elucidating the development and course of specific inner ear diseases or for perioperative characterization of cochlear implant patients.